Los juegos tradicionales en el desarrollo del aprendizaje significativo en niños de 5 a 6 años del sub nivel de preparatoria en la Unidad Educativa Fiscomisional " La Dolorosa" de la ciudad de Loja, cantón Loja perìodo 2021-2022. - Gaglay Chacan, Julissa Estephania (2022)
The purpose of this study on traditional games in the development of meaningful learning in children aged 5 to 6 in the city of Loja, Loja canton, was to apply traditional games with variants adapted to the high school curriculum, in a population of 28 children from the first parallel year "A", the sample was the entire universe, since there was easy access to this group, for this purpose the instruments used for data collection were carefully selected, which was an observation sheet made before the application of the didactic guide and after its application, obtaining extremely favorable results, in addition to this, a Google Forms survey of 8 questions was used to teachers of said institution, the same as in the development of this work, the analyzes and results obtained were found, In general, the pedagogy proposed in the objectives was a success, since it was carefully applied in a time of 45 minutes. utes each class obtaining positive achievements, concluding that traditional games inescapably influence the development of meaningful learning.